A 4-years monitoring of Hypoderma diana in horses from the Czech Republic - Kudrnáčová, Marie; Langrová, Iva; Maršálek, Miroslav; Jankovská, Ivana; Scháňková, Stěpánka; Brožová, Adéla; Truněčková, Jana (Parasitology research, 2014)
The occurrence of Hypoderma diana (Diptera: Hypodermatidae) in a herd of 15 horses was observed during a 4-year period (2010-2013) in northwest Bohemia. During this period, infestation by the warble fly H. diana increased from 12.5% in 2010 to 53.3% in 2013. Nodules were observed on the neck, back, stomach, legs, and head. The incidence of H. diana was probably influenced by the presence of a specific host mouflon (Ovis orientalis musimon).
Keywords: Horses; Sheep, Domestic; koně; Hypodermyiasis; hypodermyiáza; Female; Horse Diseases; Animals; ženské pohlaví; Česká republika; nemoci koní; mužské pohlaví; Male; Diptera; zvířata; ovce domácí; Czech Republic